Relations with the European Union and the United Kingdom Post-BREXIT: Perspectives from the Caribbean - Jessica Byron (Études Caribéennes)
The article explores the implications of BREXIT for CARIFORUM states and UK Caribbean territories. It stresses that all conclusions are subject to change since the BREXIT talks are ongoing and the situation is fluid. It shows the diverse levels of political or economic vulnerability to BREXIT experienced by different territories and examines the options for future political and economic relations with the United Kingdom and the European Union.